2017
DOI: 10.22246/jikm.2017.38.5.610
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cardiorenal Syndrome Treated with Korean Medicine

Abstract: Objectives : The purpose of this study is to report the clinical effect of herbal medicine on the patient considering chronic renal failure. The patient complained of hemiparesis, general weakness, anorexia, nausea and dizziness. Methods : According to the traditional Korean medicine syndrome differentiation, the patient was classified as Deficiency of Spleen Qi and prescribed Bojungikki-tang and Bojungikki-tang gamibang as well as acupuncture and moxibustion treatment. Changes of BUN, creatinine, VAS for gena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…[ 34 ] An even higher reduction in thermal conductivity is observed for the plasma‐enhanced atomic layer deposition (PEALD) grown BTO thin films. [ 35,36 ] Both measurements are not consistent with our first‐principles thermal conductivity predictions. Similar discrepancy between the experimental measurements and first‐principles predictions is also observed in STO, also presented in Figure 4b.…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…[ 34 ] An even higher reduction in thermal conductivity is observed for the plasma‐enhanced atomic layer deposition (PEALD) grown BTO thin films. [ 35,36 ] Both measurements are not consistent with our first‐principles thermal conductivity predictions. Similar discrepancy between the experimental measurements and first‐principles predictions is also observed in STO, also presented in Figure 4b.…”
Section: Resultscontrasting
confidence: 61%
“…b) Thermal conductivity of BTO as a function of characteristic length. The characteristic length is equal to film thickness for this work (green squares) and PEALD BTO thin films (blue squares), [ 36 ] and grain size for ng‐BTO thin films (red squares), [ 34 ] ng‐STO thin films (brown triangles), [ 27 ] and ng‐STO ceramics (pink triangles). [ 38 ] The bulk value of BTO measured using a single crystal (black dashed line) is also shown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study revealed that only 5 of 42 patients with TD (12%) achieved remission after causative drug discontinuation. Additionally, another study reported that only 33% of patients experienced remission 2 years after causative drug discontinuation [1,7].…”
Section: Discussionmentioning
confidence: 99%